THE INFLUENCE OF ATMOSPHERE INTO RADIORANGEFINDER OBSERVATION OF ARTIFICIAL EARTH SATELLITES ( A E S) - Kablak, N. I. (Одеські астрономічні публікації, 2017)
The atmospheric refraction causes changes in the velosity retardation and in the direction of electromagnetic waves (bending) along the propagation path and introduces a delay in the time of arrival of transatmospheric signals. In the results of location of atmosphere in fine days during the year on five stations of Ukraine it is investigated the influense of wet component on to the size of atmosphere error by measusuring of distance to satellites in radiorange. Radiosonde data are used to examine the accuracy of several models for wet component of tropospheric delay prediction on the base of surfase meteorological measurements.